The Future of Electric Vehicles: Navigating the Intersection of AI, Cloud Technology, and Cybersecurity - Rehan, Hassan (International Journal of Scientific Research and Management (IJSRM), 2024)
The emergence of electric vehicles (EVs) represents a paradigm shift in transportation, offering not only the promise of reduced carbon emissions but also the potential for enhanced sustainability and innovation. However, the full realization of EVs' transformative capabilities extends beyond mere electrification; it encompasses the integration of state-of-the-art technologies such as Artificial Intelligence (AI) and Cloud Computing. This meticulously crafted research article delves into the profound impact of AI and cloud technologies on the EV landscape within the United States. It meticulously examines how these technological advancements are reshaping EV ecosystems, catalyzing advancements in autonomous driving, optimizing battery management systems, and enriching user experiences. Furthermore, it elucidates the imperative need for robust cybersecurity measures to fortify these sophisticated systems against cyber threats, thereby ensuring the integrity, privacy, and stability of the transportation network.With a diverse audience in mind, including automotive industry professionals, policymakers, cybersecurity experts, environmental advocates, technology enthusiasts, and the broader public, this article serves as a beacon illuminating the future of transportation, sustainability, and digital security within the realm of EVs. Through a blend of rigorous analysis, insightful commentary, and visionary foresight, it aims to provide profound insights into the trajectory of EV technology in the United States and beyond.